The Kulture-Lige`s Role in the Yiddish Language Development in Ukrainian People’s Republic and the Early Soviet Period: From the Epoch of Experimentation to Ideological Restrictions - Umanska, Anna (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
The purpose of the research: The proposed article aims to highlight the contribution of the educational organization Kultur-Lige to the development of the Yiddish language in the Ukrainian People’s Republic and the early Soviet period. Methods of the research: The methodological basis of the research is Karl Mannheim`s theory of generations, helping to analyze the motivational aspirations of the Kultur-Lige figures in the context of the Yiddish culture creation. Scientific novelty: The novelty of the research lies in the specification of a topic that was not covered in the national scientific literature. In addition, the study analyzed several Yiddish-language sources that still need to be introduced into the national scientific community. Conclusions: During the Kultur-Lige formation in the period of Ukrainian People’s Republic and the first years of the Soviet regime, the creation of Yiddish educational institutions, and the development of literature and theatre were free and experimental. However, with the Soviet establishment, cultural policy towards Yiddish began to transform. The authorities began to dictate the course of development to all Jewish organizations, which led to the liquidation of the Kultur-League and the actual eradication of national elements from Yiddish culture and education.